AN ANALYSIS OF THE THEME OF LOVE AND DEATH IN JOHN DONNE'S POETRY - Sadullaev Feruz Bakhtiyorovich; Qilicheva Zevarxon (American Journals Publishing, 2024)
This article is aimed to discuss the poetry of one of the greatest minds in English literature, the metaphysical genius John Donne. Donne`s writing is very complicated and rarely holds a single meaning. His poetry includes a lot of different subjects, out of which we discuss the ones including love or/and death. In this paper we are going to speak about the critics' views, both the ones that consider Donne's love poetry to be a result of his metaphysical studies and those that write about Donne`s “true self”. This paper discusses all the various ways of love that Donne writes about and all the different types he challenges death. Furthermore, we analyze the poems in which Donne mixes love and death together, as a result, he never allows death to "win". Moreover, by making analysis of Donne`s poems we will try to explore “the writers soul”.
Keywords: Love, death, spiritual peace, religion, holy, the power of love, contempt, cynicism, bitterness, sarcasm.